Analysis of a Drug Logistics Sop Model to Ensure Drug Availability (Qualitative Study: at the Pharmacy Installation of Ayamaru Public Health Center Southwest Papua) - Anasthasia F M Ayomi; Erliany Syaodih; Yen Efawati (Jurnal Multidisiplin Sahombu, 2025)
The availability of medicines in health facilities is a key indicator of effective and quality health services. However, in many Community Health Centers (Puskesmas), including Ayamaru Puskesmas in Southwest Papua, drug stock instability often occurs due to weak operational procedures (SOP) for drug logistics. This study aims to analyze the implementation of the drug logistics SOP model in ensuring drug availability at the Ayamaru Community Health Center Pharmacy Installation through a qualitative approach. The research method used was a qualitative case study, with data collection techniques including in-depth interviews with pharmacy staff, direct observation of the logistics management process, and documentation of related documents such as stock records, drug requests, and distribution. Data analysis was conducted thematically based on aspects of the logistics SOP, including planning, receiving, storing, distributing, and recording drugs. The results showed that although the drug logistics SOP was in place, its implementation still faced obstacles such as limited human resources, delayed distribution from the district health office, and a lack of training and routine supervision. Furthermore, the recording and reporting system was largely manual, making it prone to errors and information delays. Therefore, strengthening the capacity of pharmacy staff, optimizing the logistics information system, and institutional commitment to consistently implementing the SOP are necessary. Therefore, understanding and improving the drug logistics SOP model can be key to ensuring sustainable drug availability at the Ayamaru Community Health Center, supporting equitable and quality access to healthcare services for the local community.